Auroral Electrojet Activity for Long‐Duration Radial Interplanetary Magnetic Field Events. Issue 3 (7th March 2023) - Park, Jong‐Sun; Shi, Quan Qi; Shue, Jih‐Hong; Degeling, Alexander W.; Nowada, Motoharu; Tian, An Min; Kim, Khan‐Hyuk; Pitkänen, Timo; Gjerloev, Jesper W.
Abstract: In this paper, we provide statistical evidence that the level of solar wind‐magnetosphere‐ionosphere (SW‐M‐I) coupling is weaker under radial (Sun‐Earth component dominant) interplanetary magnetic field (IMF) conditions than non‐radial IMF conditions. This is performed by analyzing auroral electrojet activity (using SuperMAG auroral electrojet indices) in the sunlit and dark ionospheres for long‐duration (at least 4 hr) radial IMF events and comparing against the same for long‐duration azimuthal (dusk‐dawn component dominant) IMF events. We show that the north‐south IMF component (IMF B z ) plays a crucial role in controlling the level of auroral electrojet activity as a negative half‐wave rectifier even for both IMF orientation categories. However, it is found that the magnitudes of the auroral electrojet indices are generally lower for radial IMF than for azimuthal IMF under similar sets of solar wind (radial bulk velocity and number density) and IMF B z conditions, regardless of whether these indices are derived in the sunlit or dark regions. Moreover, the efficiency of coupling functions is lower for radial IMF than for azimuthal IMF, implying that increased coupling strength due to the azimuthal IMF component alone cannot well explain weaker auroral electrojets during radial IMF periods. Lastly, the contribution of the radial IMF component itself to auroral electrojet activity is also lower compared to the azimuthal IMF component. Our results suggest that the level of SW‐M‐I coupling characterized by auroral electrojet activity can be modulated by the radial IMF component, although the effect of this component is weaker than the other two IMF components. Plain Language Summary: The ionospheric electric current that flows along the auroral oval, called the auroral electrojet, is one of the manifestations of solar wind energy transfer into the magnetosphere‐ionosphere system via magnetic reconnection processes between the interplanetary and terrestrial magnetic field lines. Previous studies mainly focused on the role of interplanetary magnetic field (IMF) orientation in the plane perpendicular to the Sun‐Earth line (approximately solar wind flow direction) in controlling auroral electrojet activity, based on the dayside magnetopause magnetic field topology viewed from the Sun. In this study, we turn our attention to auroral electrojet activity under radial (nearly parallel to the Sun‐Earth line) IMF conditions by statistically examining the SuperMAG auroral electrojet indices for radial IMF intervals and comparing them with those for non‐radial IMF intervals under similar sets of interplanetary conditions. Our statistical results reveal that both the auroral electrojet intensity and the coupling efficiency between interplanetary and auroral electrojet parameters are lower under radial IMF conditions than non‐radial IMF conditions. These findings indicate that the radial component of the IMF can modulate the level of solar wind‐magnetosphere‐ionosphere coupling, although its effect is weaker than the other IMF components. Key Points: Auroral electrojet intensity is typically lower for radial interplanetary magnetic field (IMF) than for azimuthal IMF under similar IMF B z and solar wind conditions Increased coupling strength due to IMF B y alone cannot well explain weaker auroral electrojets during radial IMF compared to azimuthal IMF The level of solar wind‐magnetosphere‐ionosphere coupling can be modulated by the radial IMF component as well as the other two IMF components